Evaluation of readability of Turkish websites about smoking cessation - Solak, İbrahim and Kozanhan, Betül and Akın, Ayşenur and Gürer, Nursena and Ay, Enes and Eryılmaz, Mehmet Ali (Journal of Dependence, 2021)
Objective: This study aimed to examine the readability levels and contents of Turkish websites on smoking cessation. Method: A search was performed in August 2019 by typing the word “smoking cessation” in Google search engine (https://www.google.com). Commercial websites, advertisement websites, chat websites, forum websites, magazine websites, websites containing only images or videos, and websites with less than 10 sentences were excluded from the study. The readability levels of Turkish websites on smoking cessation were determined according to the Ateşman and Bezirci-Yılmaz readability formulas. Results: A total of 62 websites (23 (37.1%) in the first group and 39 (62.9%) in the second group) were included in the study. The median Ateşman and Bezirci-Yılmaz readability values were respectively 48.47 and 13.08. The median number of sentences was 34.00. The median number of words was 439.00. Conclusion: This study found that the readability level of Turkish websites on smoking cessation was “difficult” according to the Ateşman readability formula and at “undergraduate level” according to the Bezirci-Yılmaz readability formula. These results are fairly higher than the education level of Turkish people.